Determinación de la presencia de Dermatofitos asociados a Micosis superficiales en caninos del cantón Yantzaza - Valdiviezo Romero, Jonnathan Oscar (2024)
The Yantzaza canton has a hot-humid climate, which favors a favorable environment for the presence of mycosis in canines, these are conditions that cause long-term damage to the animals, being a risk for the owners since they are considered zoonotic transmitted diseases and their growth is associated with high temperatures and humidity, therefore, we proposed to identify fungi of dermatophytes genus associated with superficial mycosis in canines in the Yantzaza canton. For which 70 animals were evaluated considering physical variables and skin lesions associated with the presence of fungi on the skin, for which microbiological cultures were performed in selective media for fungal growth and subsequent identification by microscopy. Trichophyton spp was identified as the main dermatophyte present in canines and mixed lesions were evidenced in a higher proportion. Age was associated with age as a predisposing factor, being geriatric dogs those with a higher presence of lesions caused by fungi, obtaining a P value of 0.001, while there was no statistical difference between sex, breed, place of stay, and body condition with the association to the presence of dermatophytosis.